1991
DOI: 10.1177/104438949107200205
|View full text |Cite
|
Sign up to set email alerts
|

Initial Impact of Plant Closings on Automobile Workers and Their Families

Abstract: Unemployment caused fry plant closings continues to have a severe impact on automobile workers and their families. Specific findings from the first-year survey data of a longitudinal research project investigating this problem are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…From 1979 to 1985, more than 11.5 million workers lost their jobs because of plant closings (Hoffman et al, 1991;Mishel and Simon, 1988). Dislocated workers experience high levels of unemployment, longer-thanaverage spells of joblessness, and reductions in earnings.…”
Section: Downloaded By [Uzh Hauptbibliothek / Zentralbibliothek Züricmentioning
confidence: 99%
“…From 1979 to 1985, more than 11.5 million workers lost their jobs because of plant closings (Hoffman et al, 1991;Mishel and Simon, 1988). Dislocated workers experience high levels of unemployment, longer-thanaverage spells of joblessness, and reductions in earnings.…”
Section: Downloaded By [Uzh Hauptbibliothek / Zentralbibliothek Züricmentioning
confidence: 99%
“…However, while economic distress can be associated with mental health problems, other US researchers have noted that some coping resources and behaviours buffered distress while others exacerbated it (Yeung & Hofferth 1998). The US comparison study by Broman and colleagues (Broman et al 1990; see also Hoffman et al 1991), found severely strained coping mechanisms among redundant workers and their families, with financial hardship being the key factor in job loss stress on families. They also found the relationship between job loss and financial hardship was mediated by marriage, whereby married workers also tended to have less money saved, a mortgage and dependent children.…”
Section: Financial Strainmentioning
confidence: 99%
“…Psychologically, unemployed individuals are seriously affected by prolonged job loss and demonstrate more frequent symptoms of poor mental health (Hoffman, Carpentier-Alting, Thomas, Hamilton, & Broman, 1991;Kokko & Pulkkinen, 1998;Wanberg, 1997). Depression seems to be the most widely reported psychological symptom (Archer & Rhodes, 1993;Lang, 1995).…”
mentioning
confidence: 98%